Comparação da compreensão de prosódia emocional entre pessoas com transtornos do espectro do autismo e pessoas com desenvolvimento típico - Cicuti, Talita de Freitas (2017)
People diagnosed with Autism Spectrum Disorder (ASD) present deficits on the recognition of emotions in the categories of face, emocional prosody and corporal communication. Althought the literature suggests losses on the recognition of emotional prosody, there are still divergences on this statement. The purpose of this study was to evaluate the abilities of emotional prosody recognition by means of pronouncements in people with ASD and to compare them with people with a typical development, considering ages from 18 to 35 years old. For this purpose, the WASI scale and its four subtests (verbal and execution) were used as the IQ measure, a Screening scale (Autism Screening Questionaire – ASQ), and for conducting the tests, voices were used in three separated tests. In the first one, the voices presented the same emotional content described on the sentence's semantics. As to the second test, the voices presented different emotional content regarding the semantics of each sentence. Finally, in the third examination, there was no semantic content implicit in the sentences, having the pronouncements been recorded with emotional variation of voices. Evidence suggests that people with ASD struggle on the emotional prosody recognition, in the three performed tests, besides presenting low specific emotions recognition index.